2014
DOI: 10.1007/s00429-014-0926-2
|View full text |Cite
|
Sign up to set email alerts
|

White matter pathway supporting phonological encoding in speech production: a multi-modal imaging study of brain damage patients

Abstract: In speech production, an important step before motor programming is the retrieval and encoding of the phonological elements of target words. It has been proposed that phonological encoding is supported by multiple regions in the left frontal, temporal and parietal regions and their underlying white matter, especially the left arcuate fasciculus (AF) or superior longitudinal fasciculus (SLF). It is unclear, however, whether the effects of AF/SLF are indeed related to phonological encoding for output and whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Additionally, we found that the electrode impacted the three (Schmahmann et al, 2007). This tract has been found to be associated with language articulation (Han et al, 2016;Johnson et al, 2015), processing speed (Kerchner et al, 2012), and working memory (Vestergaard et al, 2011). For instance, the superior longitudinal fasciculus has been identified to contribute to VF performance in schizophrenia (Peters et al, 2012) since reduced integrity of the superior longitudinal fasciculus correlated with poorer VF.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Additionally, we found that the electrode impacted the three (Schmahmann et al, 2007). This tract has been found to be associated with language articulation (Han et al, 2016;Johnson et al, 2015), processing speed (Kerchner et al, 2012), and working memory (Vestergaard et al, 2011). For instance, the superior longitudinal fasciculus has been identified to contribute to VF performance in schizophrenia (Peters et al, 2012) since reduced integrity of the superior longitudinal fasciculus correlated with poorer VF.…”
Section: Discussionmentioning
confidence: 79%
“…SLF II links caudal part of the inferior parietal lobule and various dorsolateral and ventrolateral frontal regions whereas the more ventral component, SLF III, connects the supramarginal gyrus with the ventral premotor and prefrontal cortex (Schmahmann et al, ). This tract has been found to be associated with language articulation (Han et al, ; Johnson et al, ), processing speed (Kerchner et al, ), and working memory (Vestergaard et al, ). For instance, the superior longitudinal fasciculus has been identified to contribute to VF performance in schizophrenia (Peters et al, ) since reduced integrity of the superior longitudinal fasciculus correlated with poorer VF.…”
Section: Discussionmentioning
confidence: 99%
“…The dissimilarity between images was computed by 1 minus Jaccard similarity. For the phonological RDM, the dissimilarity of two-item names was measured by 1 minus the proportion of shared sub-syllabic units (onset or rhyme), regardless of position (e.g., [ 57 ]). The sub-syllabic units for a given syllable were defined based on the phonetic transcript of Chinese characters (the “pinyin” system), which transcribes each syllable with an onset consonant (“shengmu”) and a rhyme vowel or vowel-consonant (“yunmu”).…”
Section: Methodsmentioning
confidence: 99%
“…The dorsal pathway consists of the superior longitudinal fascicle (SLF) and arcuate fascicle (AF), and is responsible for sound-to-motor mapping ( 13 , 14 ). Stroke involving these bundles can lead to dysfunction in speech production and a decreased aphasia quotient (AQ) ( 15 18 ). The dorsal route was once considered the dominant pathway in linguistic processing, until higher-level language comprehension was found to be mediated by the ventral stream ( 19 ), which consists of the inferior fronto-occipital fascicle (IFOF), uncinate fascicle (UF), and inferior longitudinal fascicle (ILF).…”
Section: Introductionmentioning
confidence: 99%